Melanocortin System in Kidney Homeostasis and Disease: Novel Therapeutic Opportunities - Chang, Mingyang; Chen, Bohan; Shaffner, James; Dworkin, Lance D.; Gong, Rujun (Frontiers in Physiology, 2021)
Melanocortin peptides, melanocortin receptors, melanocortin receptor accessory proteins, and endogenous antagonists of melanocortin receptors are the key components constituting the melanocortin hormone system, one of the most complex and important hormonal systems in our body. A plethora of evidence suggests that melanocortins possess a protective activity in a variety of kidney diseases in both rodent models and human patients. In particular, the steroidogenic melanocortin peptide adrenocorticotropic Hormone (ACTH), has been shown to exert a beneficial effect in a number of kidney diseases, possibly via a mechanism independent of its steroidogenic activity. In patients with steroid-resistant nephrotic glomerulopathy, ACTH monotherapy is still effective in inducing proteinuria remission. This has inspired research on potential implications of the melanocortin system in glomerular diseases. However, our understanding of the role of the melanocortinergic pathway in kidney disease is very limited, and there are still huge unknowns to be explored. The most controversial among these is the identification of effector cells in the kidney as well as the melanocortin receptors responsible for conveying the renoprotective action. This review article introduces the melanocortin hormone system, summarizes the existing evidence for the expression of melanocortin receptors in the kidney, and evaluates the potential strategy of melanocortin therapy for kidney disease.